PENDAMPINGAN PENYUSUNAN BORANG AKREDITASI MADRASAH TSANAWIYAH SAHABAT CENDIKIA KOTA TERNATE - Mardia Hi Rahman; Saiful Latif; Ade Haerullah (EDUKASI, 2022)
Madrasah Tsanawiyah Sahabat Cendikia (MTs SC) Ternate is one of the schools that has not been accredited. Actually, the eight components of the national education standard have been implemented by MTs SC, but the documents and activity reports are not well administered. The results of interviews with partner madrasah principals obtained the same problem, namely the low value of each component of the SNP which refers to the accreditation instrument. Training programs and assistance in the preparation of accreditation forms by the community service team are the solutions offered to help partner school problems. The stages of this community service program include: (1) the training stage, (2) the stage of assisting the preparation of the accreditation form, (3) the stage of assisting the fulfillment of the physical documents of accreditation, (4) the evaluation stage. Training in the fulfillment of physical documents and supporting documents provides understanding and skills to the form drafting team in preparing physical documents and supporting documents in accordance with technical instructions and a list of needs that have been made previously. Training through tutorials on how to fill out instruments through the IASP 2020 application provides understanding and skills to the form-writing team on how to use the application